Kajian terhadap sifat mekanik bagi jenis corak pengisian dalam proses pembuatan tiga demensi - Shamsudin, Muhamad Khairy (2014)
This project is regarding the study of mechanical properties that have on the model that produced by Makerbot Replicator 2 machine. This machine apply Fused Deposition Modelling (FDM) technology where the 3D model fabricate with different infill pattern such hexagonal, linear, marrocanstar and catfill. The determination of percentage infill is 20%, 40%, 60% and 80%. All spesimen are fabricate according to the ISO standard for tensile test and flexure test. The results show that marrocanstar have high tensile strength with value 589.41N for maximum force and percentage infill at 80%, while for flexure strength, infill pattern marrocanstar with value 108.82N at percentage infill 40%.